The effects of Er × Bt drift on LH wave coupling with divertor configuration at EAST. (11th June 2021) - Li, Y C; Ding, B J; Li, M H; Wang, M; Liu, L; Wang, Y F; Wu, C B; Yan, G H; Kong, E H; Zhang, L; Liu, S C; Lin, X D; et al.
Abstract: The coupling characteristics of the 4.6 GHz lower hybrid (LH) grill and the factors affecting LH wave coupling, mainly E r × B t drift, with divertor configuration in anti-clockwise/clockwise magnetic field direction are studied. Based on the Langmuir probe measurement, the relationship between the reﬂection coefficient (RC) of LH power and the edge density at the grill mouth ( n e, grill ) measured by Langmuir probes is investigated. The optimum LH wave coupling with RC less than 2% is achieved when n e, grill is in the range of 1 × 10 18 m − 3 – 2 × 10 18 m − 3, which is quite close to the theoretically predicted value. In addition, the experimental results show that E r × B t drift in the divertor scrape off layer plays a dominant role in affecting n e, grill and LH wave coupling. Studies show that the discrepancy in n e, grill and LH wave coupling in different magnetic field directions is mainly attributed to the different directions of E r × B t drift, whereas the corresponding discrepancy with different plasma currents is mainly ascribed to the change in E r × B t drift intensity. Therefore, for the upper single null divertor configuration, a lower/higher plasma currents is more favorable for increasing n e, grill and improving LH wave coupling in anti-clockwise/clockwise B t . The above studies are of great significance for optimizing and improving LH wave coupling in the extension of the plasma operation regime.